Cretaceous-Cenozoic growth of the Patagonian broken foreland basin, Argentina: Chronostratigraphic framework and provenance variations during transitions in Andean subduction dynamics - Butler, Kristina L. (2020)
The Cretaceous-Cenozoic evolution of the Patagonian broken foreland basin system at 42–43°S in the northern Chubut province of Argentina is associated with variable retroarc phases of fold-thrust belt shortening, extension, and basement uplift during changes in the dynamics of oceanic slab subduction. Basement inheritance and progressive shallowing of an east-dipping subducting slab are important mechanisms of foreland partitioning, as dictated by the preexisting (pre-Andean) structural architecture and forelandward (eastward) advance of Late Cretaceous arc magmatism. Previously recognized growth strata help define the timing of fold-thrust belt shortening and retroarc basement-involved uplift, but the precise consequences for sediment routing remain poorly understood, with uncertainties in patterns of basin evolution before, during, and after shallowing and resteepening of the subducting slab. In this study, distinctive sediment source regions and magmatic histories enable evaluation of the stratigraphic and tectonic evolution of the retroarc foreland basin using new provenance results, maximum depositional ages, and isotopic signatures from detrital zircon U-Pb geochronology and Lu-Hf geochemical analyses. A compilation of published bedrock crystallization ages and distributions of metamorphic and igneous basement rocks identify: a western source region defined by the Andean magmatic arc and associated pre-Andean basement; and an eastern source region consisting of intraplate magmatic units and the North Patagonian Massif. We demonstrate that Aptian-Cenomanian retroarc basin fill was derived principally from the basement massif and intraplate volcanic units to the east, followed by a Late Cretaceous (Campanian-Maastrichtian) reversal in sedimentary polarity and subsequent exclusive derivation from the Andean arc and orogenic belt to the west. Late Cretaceous-Paleocene slab shallowing and arc cessation was succeeded by late Eocene–earliest Miocene extension during slab rollback and renewal of arc magmatism. Thereafter, Miocene sedimentation was closely linked to shortening in the Andean fold-thrust belt. Within the retroarc succession, new U-Pb ages provide estimates of depositional ages for Lower Cretaceous through Miocene stratigraphic units. Finally, in addition to U-Pb provenance and chronostratigraphic constraints, zircon Hf isotopic signatures from the detrital record provide confirmation of a Cretaceous-Cenozoic history involving: (1) initial establishment of a continental magmatic arc; (2) transition from a neutral to compressive tectonic regime; (3) shallowing of the subducting slab and arc cessation during retroarc basement partitioning; (4) arc retreat and foreland basin abandonment during slab rollback (with modest extension and crustal thinning); and (5) final renewed shortening during arc rejuvenation.